La evaluación en letras del tiempo. Lo publicado en prensa escrita: selección de algunos artículos - González Jiménez, Dulfay Astrid (Editorial Bonaventuriana, Universidad de San Buenaventura Cali., 2011)
La evaluación en letras del tiempo is the third publication in this format of the Grupo de Investigación en Evaluación y Calidad de la Educación-Giece on what the written press reports about the evaluation of learning carried out by the Colombian State through the ICFES by means of standardized tests of a sampling and census nature. What was published in the press shows that education is indeed a media issue and that, given its impact on imaginaries and social representations, evaluation is mobilizing, it is a device that makes others talk about education and makes education talk about what it says today in a different way about itself and with a language that was previously alien to it: indicators, quality, accreditation, measurement, competencies, internationalization, human capital, performance, among others.